Effects of sugarcane bagasse ash (SCBA) on the strength and compressibility of cement stabilized peat - M. K. Abu Talib; N. Yasufuku; R. Ishikura (Lowland Technology International, 2015)
This research objective is to evaluate effectiveness of sugarcane bagasse ash (SCBA) inclusion in peat stabilization. To develop the optimal mix design, stabilized peat specimens were tested in unconfined compression. Energy Dispersive Xray (EDX) and Scanning Electron Microscope (SEM) apparatus was used to examine elemental composition and microstructure. Consolidation tests were carried out in a standard Oedometer apparatus on the obtained optimum peat-cement-bagasse (PCB) mixture. It was found that stabilized peat comprising 20% partial replacement of OPC with SCBA has the maximum UCS and discovered to be about 1.2 times greater than UCS of peatcement (PC) specimen. The UCS of optimum PCB mixture specimens increased with curing duration in water. Compared to untreated soil, SEM results for stabilized peat gave the significant pore improvement. EDX results prove that lower carbon (C) and higher calcium (Ca) fractions shows the better results of strength. There was a significant reduction of void ratio (e) for optimum PCB mixtures as compared to untreated peat. It was observed that preconsolidation pressure, σ’c were increase with curing period. Results finding shows that the stabilized peat Cα/Cc ratios were decline dramatically from untreated peat which is indicating the stabilized mixture can effectively reduce the secondary compression.